Characterization of Factors Predicting a Favorable Opinion of Research Applications Submitted for an Ethical Review Process - Mirpuri, Eduardo; García-Álvarez, Lara; Acín-Gericó, María Teresa; Bartolomé, Blanca; Delgado Bolton, Roberto C.; San-Martín, Montserrat; Vivanco, Luis (Frontiers in Medicine, 2022)
Introduction: In Spain, biomedical research applications must receive a positive ethical opinion from Research Ethics Committees (RECs) before being executed. There is limited information on how to optimise the ethical review process to reduce delays. This study was performed to characterize variables predicting favourable opinions at the first ethical review performed by a REC. Material and methods: The study assessed all research applications revised by a REC in 2019-2020. Data was extracted from REC’s database of La Rioja, Spain. Variables collected covered three areas: (i) principal investigator’s profile; (ii) study design; and (iii) ethical review process. A model based on multiple logistic regression analysis was created to identify variables explaining favourable opinions in first rounds of ethical review processes. Results: The sample included 125 applications (41 submitted in 2019, and 84 in 2020). At the first review, nine (7%) applications were rejected, 56 (45%) were approved, and the remaining 60 (48%) required at least two reviews prior to approval. When comparing both years, a two-fold increase in the number of applications submitted, and a difference in the ratio of applications with a favourable versus non-favourable opinion were observed. Furthermore, a model predicted 71% of probability of obtaining a favourable opinion in the first ethical review. Three variables appeared as being explanatory: if the principal investigator is either the group leader or the department’s head (OR=17.39; p<0.001), and if the informed consent (OR=11.79; p=0.01), and methods and procedures (OR=34.15; p<0.001) are well done. Conclusions: These findings confirm an increase in the number of submissions and a difference in the ratio of applications approved by year. Findings observed also confirm deficiencies in “informed consent” and in “methods and procedures” are the two main causes of delay for favourable ethical opinions. Additionally, findings highlight the need that group leaders and heads of departments should be more involved in guiding and supervising their research teams, especially when research applications are led by less experienced researchers. Based on these findings, it is suggested that an adequate mentoring and targeted training in research could derive in more robust research applications and in smoother ethical review processes.